STRUKTUR USUS IKAN Ompok hypophthalmus (Bleeker 1846) DARI PERAIRAN SUNGAI SIAK KOTA PEKANBARU - Venny Firdasari; Yusfiati '; Roza Elvyra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ompok hypophthalmus is a freshwater fish which lives flood plain river. Siak river is one of flood plain river in Riau province. Siak river is very valuable for Pekanbaru people for household to industrial purposes. The household and industrial activity may cause the decrease of water quality. The contaminated water affects the living things in this area, such as O.hypophthalmus fish. Therefore, it is necesarry to detect the water quality decrease by observing the intestine structure of O.hypophthalmus. This study aimed to find out the histological structure of intestine tissue of Ompok hypophthalmus, especially which lives in the Siak I and Siak II bridge. This study was conducted from January to April 2014. Histological slide of O.hypophthalmus intestine were made using paraffin method and stained with Hematoxylin-Eosin (HE). The results showed that the intestine parasite infections was found in O.hypophthalmus, as well as lymphocyte stacking, villous unification, epithelium lysis, and lamina propria widening. The tissue damage in intestine might be due to the content of heavy metal above the normal standard.